2022
DOI: 10.3847/1538-4357/ac5bd8
|View full text |Cite
|
Sign up to set email alerts
|

Digging into the Interior of Hot Cores with ALMA (DIHCA). II. Exploring the Inner Binary (Multiple) System Embedded in G335 MM1 ALMA1

Abstract: We observed the high-mass protostellar core G335.579–0.272 ALMA1 at ∼200 au (0.″05) resolution with the Atacama Large Millimeter/submillimeter Array (ALMA) at 226 GHz (with a mass sensitivity of 5σ = 0.2 M ⊙ at 10 K). We discovered that at least a binary system is forming inside this region, with an additional nearby bow-like structure (≲1000 au) that could add an additional member to the stellar system. These three sources are located at the center of the gravitational potential well of the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…Observed in other high-mass star-forming HFS clouds (Liu et al 2012(Liu et al , 2022a(Liu et al , 2022bPeretto et al 2013Peretto et al , 2014Kumar et al 2020;Avison et al 2021;Sanhueza et al 2021), this dynamical mass accretion process has been highlighted in the theoretical models such as GHC and I2. Of particular mention are the two most-studied high-mass HFS clouds, SDC335 (Avison et al 2021;Olguin et al 2021Olguin et al , 2022Xu et al 2023) and G34 (Liu et al 2022a), which give detailed observational evidence in strong support of the theoretical predictions.…”
Section: Multi-scale Scenario Of High-mass Star Formationmentioning
confidence: 62%
“…Observed in other high-mass star-forming HFS clouds (Liu et al 2012(Liu et al , 2022a(Liu et al , 2022bPeretto et al 2013Peretto et al , 2014Kumar et al 2020;Avison et al 2021;Sanhueza et al 2021), this dynamical mass accretion process has been highlighted in the theoretical models such as GHC and I2. Of particular mention are the two most-studied high-mass HFS clouds, SDC335 (Avison et al 2021;Olguin et al 2021Olguin et al , 2022Xu et al 2023) and G34 (Liu et al 2022a), which give detailed observational evidence in strong support of the theoretical predictions.…”
Section: Multi-scale Scenario Of High-mass Star Formationmentioning
confidence: 62%
“…At a resolution of ∼ 1000 au by ALMA, SDC335-MM1 further fragments into at least five sources, while molecular line emission is detected in two of the continuum sources, ALMA1 and ALMA3 (Olguin et al 2021). With a more extended array configuration (a resolution of ∼ 200 au), Olguin et al (2022) found that a binary system was forming inside ALMA1, with a nearby bow-like structure ( 1000 au) which could add an additional member to the stellar system. However, those studies lack appropriate temperature tracers so the analyses of fragmentation is limited.…”
Section: Sdc335: a Prototypical Hub-filament Systemmentioning
confidence: 95%
“…To address these questions, we use the data from new ALMA observations to investigate the gas motions in a prototypical global-collapse HFS, the IRDC SDC335.579-0.292 (hereafter SDC335; Peretto & Fuller 2009). Located at 3.25 kpc (based on the method from Reid et al 2016) and containing 3.7 × 10 3 𝑀 (Anderson et al 2021), SDC335 (also IRAS 16272-4837) is a well-studied massive starforming region (Garay et al 2002;Peretto et al 2013;Avison et al 2015Avison et al , 2021Olguin et al 2021Olguin et al , 2022.…”
Section: Sdc335: a Prototypical Hub-filament Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…In spite of several studies that have investigated the formation processes of NH 2 CHO in star-forming regions, it is still an open question. In this paper, we present observations of the NH 2 CHO, HNCO, H 2 CO, and CH 3 CN ( 13 CH 3 CN) lines toward 30 high-mass star-forming regions covered by the "Digging into the Interior of Hot Cores with ALMA (DIHCA)" survey (Olguin et al 2021(Olguin et al , 2022. The typical angular resolution is 0 3.…”
Section: Introductionmentioning
confidence: 99%